2018
DOI: 10.3389/fphar.2018.01481
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of the Substrate-Selective COX-2 Inhibitor IMMA in the Animal Model of Chronic Constriction Injury

Abstract: Enhancement of endocannabinoid signaling has emerged as an attractive strategy for the treatment of pain. In addition to the well-characterized hydrolytic pathways, cyclooxygenase-2 (COX-2) mediated oxygenation is thought to be an alternative route for endocannabinoid metabolism and therefore provides a new avenue for drug intervention. In this study, we examined the therapeutic effect of indomethacin morpholinamide (IMMA), a novel substrate-selective COX-2 inhibitor, in the chronic constriction injury (CCI) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…CB2 antagonist, AM630 (3 mg/kg intraperitoneally), partially reversed IMMA's action. This compound has a complex MOA, including reduction in prostaglandin E 2 (PGE2) synthesis and CB2 activation [86]. Other studies focused on aripiprazole, an antypsychotic drug and a ligand of multiple dopamine (DA) and serotonin (5-HT) receptors.…”
Section: Painmentioning
confidence: 99%
“…CB2 antagonist, AM630 (3 mg/kg intraperitoneally), partially reversed IMMA's action. This compound has a complex MOA, including reduction in prostaglandin E 2 (PGE2) synthesis and CB2 activation [86]. Other studies focused on aripiprazole, an antypsychotic drug and a ligand of multiple dopamine (DA) and serotonin (5-HT) receptors.…”
Section: Painmentioning
confidence: 99%
“…Many studies have indicated that persistent mechanical hypersensitivity was induced in the hind paw following sciatic nerve injuries along with microglial cell accumulation in the spinal dorsal horn (SDH), and the suppression of microglial cell activation in the spinal cord significantly alleviated mechanical hypersensitivity [11][12][13]. In SDH, the increased Iba1 immunoreactivity that indicates the hyperactive states of microglia was reported to be detected as early as 20 min, peaking on day 3, and remaining at a significant level on day 7 following peripheral nerve injury [14].…”
Section: Introductionmentioning
confidence: 99%
“…Repair and regeneration after nerve injury involves a complex process of change, including inflammatory reaction, adhesion reaction, extracellular matrix synergy, regulation of neurotrophic factors on regeneration, synthesis and release of neurotransmitters, formation and extension of growth cones, and regeneration of neurons. It has been reported that drug treatment can reduce the aggregation of astrocytes and microglia in spinal dorsal horn and the infiltration of macrophages into dorsal root ganglion and sciatic nerve [36]. Anethole inhibited the activation of glial cells, decreased the secretion of pro-inflammatory cytokines to relieve the chronic nerve injury in mice [37].…”
Section: Discussionmentioning
confidence: 99%
“…in the treatment of nerve injury [36,[45][46][47][48]. In addition, the NF-κB signaling pathway is also reported as being involved in nerve injury.…”
Section: Discussionmentioning
confidence: 99%